Mechanism of inhibiting renal tubular epithelial cell transformation by silencing dendritic cell CRR7 receptor - Gao Ting-ting; Hao Xiu-ying; Wu Xiao-meng; Lu Ting; Ma Ying-huan (Linchuang shenzangbing zazhi)
Objective To explore the effect of interfering with the maturation of dendritic cell by CCR7 silencing on transformation of renal tubular epithelial cells and its mechanism.Methods After 48 h transfecting siRNA-NC and siRNA-CCR7 in DC2.4 cells, intracellular level of CCR7 protein was detected for evaluating the effect of interference.The supernatant of DCs from siRNA-CCR7 and siRNA-NC groups was collected and the levels of MCP-1,MIP-1 a and TGF-β1 in supernatant were detected by enzyme-linked immunosorbent assay（ELISA）.The expression and distribution of E-Cadherin, TGF-β1,a-SMA and vimentin in HK-2 cells in induced medium were detected by Western blot and immunofluorescence after 48 h.Results The levels of MCP-1 and TGF-β1 in DC supernatant rose markedly in silent Group（P<0.05）,but not MIP-1α（P<0.05）.The expressions of TGF-β1,vimentin and a-SMA decreased significantly in SiRNA-CCR7 + HK-2 group and the expression of E-Ca protein was markedly up-regulated as compared with that in negative control group.And the difference was statistically significant（P<0.05）.As compared with negative control group, the expression and distribution of TGF-β1,vimentin and a-SMA declined in siRNA-CCR7 + HK-2 group while the expression and distribution of E-Ca protein spiked（P<0.05）.Conclusions Mature DCs can promote the development of EMT,silence CCR7,interfere with the maturation of DCs and block the epithelial-mesenchymal transition of HK-2 cells.It is probably related with the differential content of MCP-1 and MIP-1α in supernatant.